Jarateng: Making social-ends meet by embracing public living - Bogatsu, Katlego (My University, 2014)
The aim of this thesis is to investigate the importance of public space and to explore the concept of public living. The concept behind this thesis exploration is to look at the Soweto yard called a `jarata` and to look at various configurations of a Soweto yard. The reason behind choosing a Soweto yard is to conceptualise a public space which has the essence of the sociality of a Soweto yard. The investigation will begin by exploring the concept of social space and to gain an understanding of what a `social space` is in comparison to a physical place. Over the years people have defined and redefined spaces around them. In shared spaces people have used traditions and cultures to dictate the manner in which they use these spaces and have therefore created unwritten rules in these spaces. As people redefine these spaces from their designed or intended use, they essentially create social spaces. These social spaces are not the physical spaces but they happen in the physical spaces, and are driven by events which are part of people’s social and cultural patterns. So therefore the architecture of a place is defined by the social spaces which are the events, activities and the happenings in the place, which are centred on social patterns. Place is the visible space, and space is the hidden place. The architectural response is a public space where public living can be embraced more especially for the residents of Soweto and more specifically to the residents of Mofolo Central where my site is based. The space will be an enabling space which should allow the users the freedom to carry out their traditions and social patterns. The space is also an event space which allows for a variety of recreational activities from musical events, celebrations, ceremonies and play. The design of the space also incorporates an existing old cinema and seeks to revive the cinema and develop it as a cinema and theatre. The purpose of reviving the cin- ema is to bring back a cinema-going culture to the area of Mofolo and Soweto at large. The exterior space will be an extension of the cinema and will function as an open-air cinema among other uses mentioned above. In addition there will be office spaces, trade spaces both formal and informal and recreational facilities. The design plays on the social patterns of public life in Soweto.
Keywords: City planning--South Africa--Johannesburg--Soweto.; Public spaces--South Africa|zSoweto.; Community development--South Africa--Johannesburg--Soweto.